Fall related problems in the elderly: Origins and prevention through exercise - Skondras, Γιώργος; Hatzitaki, Βασιλεία (Inquiries in Physical Education and Sport, 2003)
Falls constitute one of the major problems associated with ageing. The present review provides epidemiological evidence regarding the incidence of falls and their negative impact among the elderly. The purpose is to a) identify the major factors contributing to a fall and b) present and compare different fall prevention programs that are based on exercise. Based on the epidemiological evidence presented in this study, it is deducted that there is no systematic monitoring or estimation of the falls problem in Greek population. The causes of fall could be either associated with the degenerative changes accompanying the aging process or could also be attributed to environmental factors. It is very difficult to accurately define the pathological problems that could lead to loss of balance and this is the reason why the problem could not be handled with pharmacological treatment. At this point the great value of physical exercise programs should be considered as the best way to prevent falls. Such intervention programs could be specifically designed to meet the needs of the elderly in order to improve functional mobility and reduce the risk of falls among the elderly.